2005
DOI: 10.1111/j.1365-2788.2005.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Variables influencing the ratings of importance and use of quality of life domains and indicators by Polish professionals

Abstract: The perception of professionals cannot be overlooked when considering the development and provision of QOL-related services and supports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, QoL domains as defined by Schalock et al in the Cross Cultural Survey of Quality of Life Indicators (CCSQoLI) have been empirically investigated across the world with different results. In Poland, Otrebski [11 ] found that a professional's age, education and place of work can strongly affect the evaluation of the importance and the use of certain domains. In the component analysis of the importance ratings conducted by Xu et al [12 ] in China, two (personal development and physical well being) of the original eight factors were highly correlated and loaded onto one component.…”
Section: What Is Measured In Quality Of Life?mentioning
confidence: 99%
“…Furthermore, QoL domains as defined by Schalock et al in the Cross Cultural Survey of Quality of Life Indicators (CCSQoLI) have been empirically investigated across the world with different results. In Poland, Otrebski [11 ] found that a professional's age, education and place of work can strongly affect the evaluation of the importance and the use of certain domains. In the component analysis of the importance ratings conducted by Xu et al [12 ] in China, two (personal development and physical well being) of the original eight factors were highly correlated and loaded onto one component.…”
Section: What Is Measured In Quality Of Life?mentioning
confidence: 99%